Evaluasi Kegunaan Website Mahasiswa Universitas Amikom Purwokerto Menggunakan Metode Usability Testing - Ito Setiawan; Zulfa Ummu Hani; Serli Serli; Syawalia Rahayu; Wini Audiana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The purpose of this research is to evaluate the usability of the website by students of Amikom University Purwokerto using the usability testing method. In today's digital world, websites have become the primary tools for communication and information for educational institutions. Therefore, it is important to ensure that the website meets the needs and expectations of users. The methods used in this study include data collection through a questionnaire designed to measure five key variables: learnability, efficiency, memorability, errors, and user satisfaction. This questionnaire was distributed to students to gather comprehensive feedback regarding their experiences while using the website.The research results indicate that there are many aspects that need improvement to enhance the user experience, including ease of navigation and the speed of information delivery. The lower scores on the memorability index suggest that users experience difficulties recalling how to use certain functions after not visiting the website for a certain period. Additionally, several performance issues and errors were found that could hinder users from achieving their goals on the website. We hope that these findings can provide useful recommendations for the development of educational websites to be more efficient and user-friendly. Given the negative aspects identified, it is hoped that the user experience can be improved so that the website can function as a source of information and services for students.